Curriculum Management in Integrating Deep Learning Principles into English Language Learning at SMA Negeri 1 Sindue - Nurafni Difa (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study was motivated by the demand for educational transformation in the Merdeka Curriculum era, which emphasized student-centered learning through a deep learning approach. The study aimed to examine curriculum management in integrating deep learning principles into English language learning at SMA Negeri 1 Sindue, including impacts, opportunities, and challenges. This study employed a qualitative approach using descriptive case study method. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion, while data validity was tested using triangulation techniques. The results showed that curriculum management in integrating deep learning principles had been implemented through the stages of planning, organizing, implementation, and evaluation. The implementation of deep learning positively impacted school management, teacher professionalism, teacher-student relationships, and students’ active participation in learning. Then, supporting opportunities included curriculum policy support and school leadership commitment, teacher collaboration, the development of teacher creativity and innovation, digital technology utilization, and sustainable learning. However, several challenges were identified, including differences in teachers’ readiness, administrative workload, diverse student abilities, and limited school facilities. Therefore, strengthening teacher competencies and optimizing learning facilities were needed to ensure more effective integration of deep learning principles.